Berbagai Variabel Pengaruh terkait Rokok dan Rokok Elektrik (Pengguna Ganda) terhadap Jumlah Konsumsi Rokok Konvensional di Kota Semarang - Prasetia, Irfan Rizki; Woyanti, Nenik Kismet Nugroho (Universitas Katolik Soegijapranata, Semarang, 2024)
One way that can be taken to reduce cigarette consumption is to increase the excise rate. The Indonesian government has increased cigarette excise rates 7 times during 2016-2022, with an average increase of 12.5 percent each year. However, the increase in excise rates did not reduce the number of cigarette consumers. In Semarang City, the number of cigarette consumers actually increased throughout 2016-2021, with an average increase of 5.7 percent each year. This research aims to analyze the influence of cigarette prices, smoker's age, smoker's income, duration of cigarette consumption, and multiple users on the amount of cigarette consumption. The data used in this research are primary and secondary data obtained from respondents using questionnaires and literature studies, which were processed using ordinary least squares (OLS) cross section data regression. Based on the regression results, it is known that cigarette prices, cigarette income and multiple users influence the amount of cigarette consumption. Meanwhile, the age of the smoker and the length of time he has consumed cigarettes have no effect on the amount of cigarette consumed.: